Orbital maneuvers for a space probe around Titania - Xavier, Jadilene [UNESP] (2023)
For most space missions, it is interesting that the probe remains for a considerable time around the mission target. The longer the lifetime of a mission, the greater are the chances of collecting information about the orbited body. In this work, we present orbital maneuvers that aim to show how to avoid a collision of a space probe with the surface of Titania. Through an expansion of the gravitational potential to the second order, the asymmetry of the gravitational field due to the coefficient C22 of Titania, the zonal coefficient J2 , and the gravitational perturbation of Uranus are considered. Two models of coplanar bi-impulse maneuvers are presented. The first maneuver consists of transferring an initial elliptical orbit to a final circular orbit, and the second has the objective of transferring an initial elliptical orbit to a final orbit that is also elliptical. The lag in the inclination and semi-major axis of the orbits is investigated before performing the maneuvers. To point out the best scenarios for carrying out the maneuvers, a study is presented for different points of an orbit where transfers could be made. In addition, a maneuver strategy is presented to correct the variation of the periapsis argument. The results show that maneuvers performed a few days after integration are more economical than maneuvers performed later, a few days before the collision. The economy of the maneuvers is also demonstrated through an analysis of the ratio of the increase in speed to the lifetime.